Water absorption behaviour of kenaf reinforced unsaturated polyester composites and its influence on their mechanical properties - Rashdi, Abdalla A. Ab.; Salit, Mohd Sapuan; Abdan, Khalina; Megat Ahmad, Megat Mohamad Hamdan (Universiti Putra Malaysia Press, 2010)
Fibre reinforced composites have gained use in a variety of applications. The performances of these composites may suffer when the material is exposed to adverse environments for a long period of time. Kenaf fibre reinforced unsaturated polyester composites were subjected to water immersion tests in order to study the effects of water absorption on the mechanical properties. Composites specimens containing (10%, 20%, and 30%) weight percentages of fibre were prepared. Water absorption tests were conducted by immersing these specimens in a distilled water bath at 25°C for four months. The tensile properties of the specimens immersed in water were evaluated and compared with the dry composite specimens. A decrease in the tensile properties of the composites was demonstrated, indicating a great loss in the mechanical properties of the water-saturated samples compared to the dry samples. The percentage of moisture uptake was also increased as the percentage of the fibre weight increased due to the high cellulose content. The water absorption pattern of these composites was found to follow the Fickian behaviour.